PHATIC EXPRESSIONS FOR OPENING AND CLOSING CONVERSATIONS OF JAVANESE SOCIETY IN SURAKARTA (UNGKAPAN FATIS PEMBUKA DAN PENUTUP PERCAKAPAN MASYARAKAT JAWA DI SURAKARTA) - Ratna Susanti; Dewi Agustini (UIN Raden Mas Said Surakarta, 2017)
Good, true, and polite personality expressions reflect one's noble character. The use of the phrase when one is expressing the intent to others, should be conveyed in polite form. This politeness is reflected in the use of expressions in communication. This research aimed to identify the forms, use, and local wisdom of expression phatic opening and closing the conversation in the Java community, especially in the area of Surakarta. The research shows that variations in the forms of expression of phatic. This expression aims to start a conversation, ask permission, refine the command, grateful, subtle rejection, words of sympathy, and apologized. The result showed that in order to establish harmony in their interaction in the community and as a form of politeness, found various expressions phatic in the Java community, especially in the area of Surakarta is an expression sugeng rawuh, kula nuwun, matur nuwun, nyuwun tulung, nyuwun pangapunten, mangga, kados pundi, sugeng ...atau wilujeng ..., katuran pinarak, ndherek bingah, and ndherek belasungkawa.